Preparation method of laser-engraved wood-based photo-thermal evaporator

Through laser engraving of wood and adding stearic acid phase change materials, the problem of reducing efficiency of salt crystallization in solar evaporators is solved, efficient water evaporation and low-cost solar evaporators are achieved, and the overall performance of the evaporator is improved. .

CN119217491APending Publication Date: 2024-12-31BEIHUA UNIV

Patent Information

Application Number
CN202411660502.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-20
Publication Date
2024-12-31

AI Technical Summary

Technical Problem

During the photothermal evaporator, salt crystallization in existing solar evaporators leads to the coverage of absorbed light materials, reducing the photothermal conversion efficiency, and high material costs and large carbon footprint, limiting their large-scale applications.

Method used

The photothermal evaporator is prepared by laser engraving wood, and the salts are gradually enriched and separated by fractional evaporation structure and surface treatment, and stearic acid phase change material is added to the light absorption layer to improve the efficiency and stability of the evaporator.

Benefits of technology

The evaporation efficiency of water and brine is significantly improved, the working time of the evaporator is extended, the heat loss is reduced, the photothermal conversion efficiency is improved, and the material cost is reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119217491A_ABST
    Figure CN119217491A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a laser-engraved wood-based photo-thermal evaporator, and belongs to the field of solar-driven water evaporation. The preparation method comprises the steps of wood slice cleaning, laser engraving, SA-GO-CNTs solution preparation, laser-engraved wood top layer coating with the SA-GO-CNTs solution, drying and the like. The wood grading porous evaporator is prepared through laser treatment and the top layer design of adding the photosensitive thermal coating, heat loss is reduced through the phase change energy storage technology, solar energy can be more effectively utilized, high evaporation efficiency can be kept under the poor illumination condition, and therefore the overall performance is improved, and the wood grading porous evaporator is suitable for large-scale popularization and application. The extendable preparation method easy to prepare provides an effective solution for photo-thermal evaporation.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of solar energy driven water evaporation, and in particular relates to a preparation method of a laser engraved wood-based photothermal evaporator. Background Art

[0002] Desalination is an important way to solve the global water crisis, and its necessity is to cope with the increasingly serious problem of water shortage. Many parts of the world are facing the problem of fresh water shortage, and through the innovation of technology and methods, such as solar interfacial water evaporation technology, an effective solution to this problem is provided. Solar-driven interfacial water evaporation technology has the advantages of cleanliness, high efficiency, and high photothermal conversion efficiency, which can improve the efficiency of fresh water production and increase the supply of fresh water. The solar evaporation device is inspired by the transpiration of plants. In plants, water is absorbed through the roots, then transported through the stems and leaves, and finally evaporated into the atmosphere through the stomata. This process uses solar energy to allow plants to draw water from the soil and regulate their internal water content. Similarly, the solar evaporation device uses solar energy to heat water and evaporate it, thereby converting water from liquid to gas.

[0003] During the photothermal evaporation process, the salt concentration on the surface of the photothermal material increases and crystallization occurs. On the one hand, when salt accumulates on the evaporation interface, it covers the light-absorbing material and hinders the absorption of solar energy. This salt layer will reflect or scatter part of the sunlight, reduce the photothermal conversion efficiency of the evaporator, and then reduce the evaporation rate of water. On the other hand, salt crystallization at the evaporation interface will block the pore structure of the material, prevent water from being transported to the evaporation surface through capillary action, and slow down or even stop the evaporation rate. Therefore, it is key to control the formation of water and salt at the evaporation interface, prevent heat loss and improve the efficiency of the solar evaporator.

[0004] In addition, the vast majority of current solar evaporators are made from petroleum-based products or nanomaterials, which have a significant carbon footprint and high cost, severely restricting the feasibility of large-scale applications. Therefore, finding more sustainable materials has become a top priority. Wood is an ideal substrate for solar interfacial evaporators due to its renewable nature, high porosity, low thermal conductivity, low density, and low cost. Introducing environmentally friendly alternative materials, such as natural wood, will not only help reduce carbon emissions, but also promote the development of more sustainable solar steam power technology. Summary of the invention

[0005] The purpose of the present invention is to adopt a fractional evaporation structure and surface treatment to gradually enrich and separate salts in different layers to avoid the accumulation of salts on the main evaporation interface. Laser treatment of the top layer of wood can not only improve the photothermal conversion capacity, but also improve water transport and inhibit the formation of surface salts. In addition, the addition of stearic acid phase change material in the light absorption layer is an innovative strategy to improve the efficiency of the evaporator. The stable heat supply of the phase change material can extend the working time of the evaporator, especially in the case of unstable light, it can improve the overall efficiency of water evaporation, and release heat during the non-working stage of the evaporator (such as at night), reducing heat loss and improving the photothermal conversion efficiency.

[0006] In order to achieve the above object, the present invention provides the following technical solutions:

[0007] A method for preparing a laser engraved wood-based photothermal evaporator comprises the following steps:

[0008] Step 1), cutting the wood into 3 mm thick wood chips along the cross-section direction, and washing with deionized water to remove impurities, and then brushing the iron tannic acid ink on the upper surface of the wood;

[0009] The wood chips are placed on a CO2 laser engraving machine, which uses the laser engraving machine to convert the surface of the wood chips into a graphitized carbon layer that can absorb sunlight.

[0010] Step 2), heating and melting stearic acid in a water bath, and then dispersing CNTs (carbon nanotubes) into the stearic acid at room temperature;

[0011] Pour the graphene oxide dispersion into the above solution under magnetic stirring, continue stirring and transfer to a wide-mouth container, and dry excess water to obtain a SA-GO-CNTs solution;

[0012] Step 3), the SA-GO-CNTs solution is evenly coated on the top layer of the laser-engraved wood, and after drying in an oven, a wood photothermal evaporator decorated with the SA-GO-CNTs photothermal coating is obtained.

[0013] It should be noted that the SA-GO-CNTs coating not only enhances the light absorption capacity of the solar evaporator, but also improves the heat storage capacity, so that the solar evaporator can continue to evaporate by heat storage after losing light. Laser engraving improves the light absorption and thermal conductivity of wood, and synergizes with the SA-GO-CNTs coating to further optimize the energy utilization efficiency in the field of water evaporation.

[0014] Preferably, the wood in step 1) is poplar, and the wood substrate has a length of 2 cm, a width of 2 cm, and a height of 0.3 cm.

[0015] The graphitized carbon layer formed on the surface of laser engraved wood has good light absorption ability and is hydrophobic.

[0016] Preferably, in step 2), the mass ratio of stearic acid to carbon nanotubes is 11:1, the concentration of graphene oxide dispersion is 2 mg / ml, and the mass ratio of graphene oxide to carbon nanotubes is 1:25; the temperature of the magnetic stirring is 80°C, and the stirring time is 3h; the drying temperature is 60°C, and the drying time is 18h.

[0017] Beneficial effects of the present invention:

[0018] The present invention provides a preparation method and application of a laser-engraved wood-based photothermal evaporator. The wood evaporator prepared by top design laser processing and coating enhanced photothermal conversion has strong photothermal conversion ability and exhibits efficient water purification ability. The rough top surface is hydrophobic, which improves the salt removal performance. In addition, phase change materials are integrated in the light absorption layer, so that the photothermal evaporator can not only utilize solar energy more efficiently, but also maintain a high evaporation efficiency under poor lighting conditions, thereby improving the overall performance. The bottom layer of the photothermal evaporator retains the porous and interconnected microstructure of the wood, which is convenient for rapid water transportation. The evaporation efficiency of the photothermal evaporator for pure water is 97.5%, and the evaporation efficiency for salt water is 92.4%. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 This is a schematic structural diagram of a laser engraved wood photothermal evaporator prepared in Example 1 of the present invention;

[0020] Figure 2 The logs prepared in Example 1 of the present invention ( Figure 2 a) and laser engraving wood ( Figure 2 b) High-definition camera photos;

[0021] Figure 3 Scanning electron microscope images of the laser engraved wood (left) and the cross section of the laser engraved wood coated with SA-GO-CNTs (right) prepared in Example 1 of the present invention;

[0022] Figure 4 This is a curve showing the change of the surface temperature of the laser engraved wood-based photothermal evaporator obtained in Example 1 of the present invention over time;

[0023] Figure 5 This is the DSC curve of the laser engraved wood-based photothermal evaporator prepared in Example 1 of the present invention. DETAILED DESCRIPTION

[0024] The specific embodiments of the present invention are described more clearly below in conjunction with the accompanying drawings. The examples described are only some examples of the present invention, not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0025] Example 1

[0026] A preparation method and application of a laser engraving wood-based photothermal evaporator, comprising:

[0027] (1) Laser engraving wood:

[0028] Cut the wood into 3mm thick natural wood chips (2*2*0.3cm) along the cross-section direction, then rinse the chips with deionized water to remove impurities. Mix ferric citrate with excess tannic acid and brush it on the upper surface of the wood chips. The expansion of ferric tannic acid ink under heating conditions and its catalytic properties are used to reduce excessive exposure of the wood to heat energy and enhance the contrast and accuracy of the carving.

[0029] The wood chips coated with iron tannic acid ink are placed on a CO2 laser engraving machine, and the surface of the wood chips is converted into graphite carbon material that can absorb solar energy through computer-controlled parameters to obtain laser-engraved wood.

[0030] (2) SA-GO-CNTs coating:

[0031] Stearic acid (5.5 g) was heated and melted in a water bath, and then 0.5 g of carbon nanotubes were dispersed in the stearic acid at room temperature. Graphene oxide dispersion (10 ml, concentration of 2 mg / ml) was poured into the above solution under magnetic stirring and stirred at 80°C for 3 hours. Finally, the mixture was transferred to a wide-mouth container and placed at 60°C for 18 hours to evaporate excess water to prepare a SA-GO-CNTs composite coating.

[0032] (3) Photothermal evaporator:

[0033] The SA-GO-CNTs solution was brushed on the top layer of the laser-engraved wood to form a uniform coating. After drying in an oven, a laser-engraved wood-based photothermal evaporator decorated with the SA-GO-CNTs coating was obtained.

[0034] Example 2

[0035] Compared with Example 1, Example 2 changes the processing method before laser engraving, and the rest is the same as Example 1;

[0036] The wood was cut into 3 mm thick natural wood chips (2*2*0.3 cm) along the cross-sectional direction, and then the chips were rinsed with deionized water to remove impurities;

[0037] The wood chips are placed on a CO2 laser engraving machine, and the computer controls the parameters to convert the surface of the wood chips into graphite carbon material that can absorb solar energy to obtain laser engraved wood.

[0038] Example 3

[0039] Compared with Example 1 and Example 2, Example 3 does not perform laser engraving on wood, and the rest is the same as Example 1;

[0040] The wood was cut into 3 mm thick natural poplar pieces (2*2*0.3 cm) along the cross-sectional direction, and then the poplar pieces were rinsed with deionized water to remove impurities;

[0041] The SA-GO-CNTs solution was brushed on the top layer of the wood chip to form a uniform coating. After drying in an oven, a wood-based photothermal evaporator decorated with the SA-GO-CNTs coating was obtained.

[0042] Example 4

[0043] Compared with Example 1, Example 2 and Example 3, Example 4 did not apply the SA-GO-CNTs solution, that is, the laser engraving of Example 1 was used to engrave wood.

[0044] Figure 1 This is a schematic structural diagram of a laser engraved wood-based photothermal evaporator prepared in Example 1 of the present invention;

[0045] Figure 2 This is a high-definition camera photo of the laser engraved wood obtained in Example 1 of the present invention. Figure 2 It can be seen that due to the high temperature of the laser pulse, the color of the top of the wood changes from light brown to black;

[0046] Figure 3 The following are scanning electron microscope images of the cross-section of the laser engraved wood and the SA-GO-CNTs coated laser engraved wood prepared in Example 1 of the present invention. Figure 3 It can be seen that the components of laser-treated wood, mainly lignin, cellulose and hemicellulose, are converted into carbon layers under the action of laser pulses, but the dense and ordered porous structure of the wood is still maintained. The pores of the wood in the laser-engraved wood coated with SA-GO-CNTs are preserved, and the wooden container can transfer water through capillary action. SA-GO-CNTs successfully cover the top layer of laser-engraved wood, and the surface of the evaporator becomes significantly rough, which further enhances the light absorption capacity of the top layer, which is beneficial to improve the evaporation efficiency of the evaporator;

[0047] Figure 4 The surface temperature of the laser engraved wood-based photothermal evaporator prepared in Example 1 of the present invention changes with time. During the test, an infrared camera was used to record the change in the surface temperature of the evaporator within 450 seconds when the solar irradiance was 2.0. The surface temperature of the photothermal evaporator rose from 16.2°C to 79.8°C within 170s. The temperature increase accelerated the evaporation of water, indicating that the photothermal evaporator has good photothermal conversion performance and thermal insulation performance.

[0048] Figure 5This is the DSC curve of the laser engraved wood-based photothermal evaporator prepared in Example 1 of the present invention. The latent heat of the photothermal evaporator reaches 70.312 J / g. The presence of stearic acid as a heat storage material can store a certain amount of conversion heat, thereby enhancing the evaporation rate after extinction.

[0049] Table 1 shows the water evaporation rate and evaporation efficiency of the wood-based photothermal evaporator under simulated solar irradiation, and Table 2 shows the evaporation rate and evaporation efficiency of the brine. During the evaporation process, the porous structure of the lower layer of wood in the photothermal evaporator allows water to be continuously and quickly transported from the bottom of the evaporator to the surface for evaporation. During the steam generation process, the converted heat will inevitably be dissipated into bulk water and the surrounding environment through convection, radiation, conduction, etc., reducing the steam efficiency of solar energy. At this time, the phase change material stearic acid added to the absorption layer can store part of the heat through latent heat storage, effectively reducing heat loss. It can be seen from Tables 1 and 2 that the wooden photothermal evaporator prepared in Example 1 under 2 suns (light intensity is about 200mW / cm 2 ) has a water evaporation rate of 2.89 kg·m -2 h -1 The evaporation rate of salt water is 1.75 kg·m -2 ·h -1 , the overall trend is basically consistent with the temperature change process under simulated sunlight, which proves its good photothermal response ability; the evaporation rate and evaporation efficiency of the photothermal evaporator prepared in Example 3 and Example 4 are significantly lower than those in Example 1, which further illustrates that the photothermal coating in Example 1 works synergistically with the graphitized carbon layer on the surface of the wood to enhance water evaporation. Compared with Example 1, the laser engraved wood prepared in Example 2 has insufficient laser engraving and a low degree of carbonization on the wood surface, resulting in poor light absorption ability than the laser engraved wood prepared in Example 1, which in turn leads to poor evaporation effect. It can be seen from Tables 3 and 4 that due to the latent heat storage capacity of the SA in the photothermal coating, the wood photothermal evaporator prepared in Example 1 can still maintain 0.62 kg·m -2 ·h -1 The water evaporation rate is 0.58 kg·m -2 h -1 The brine evaporation rate is better than that of other embodiments.

[0050] Table 1 Water evaporation rate and evaporation efficiency (with light) of the embodiment

[0051] Example <![CDATA[Evaporation rate (kg·m -2 ·h -1 )]]> Evaporation efficiency (%) Example 1 2.89 97.5 Example 2 2.15 73.7 Example 3 1.96 71.1 Example 4 1.74 59.4

[0052] Table 2 Evaporation rate and evaporation efficiency of salt water in the embodiment (with light)

[0053] Example <![CDATA[Evaporation rate (kg·m -2 ·h -1 )]]> Evaporation efficiency (%) Example 1 1.75 92.4 Example 2 1.38 65.4 Example 3 1.30 63.6 Example 4 0.54 39.2

[0054] Table 3 Water evaporation rate and evaporation efficiency (without light) of the embodiment

[0055] Example <![CDATA[Evaporation rate (kg·m -2 ·h -1 )]]> Evaporation efficiency (%) Example 1 0.62 38.6 Example 2 0.48 26.3 Example 3 0.49 26.7 Example 4 0.29 14.1

[0056] Table 4 Water evaporation rate and evaporation efficiency (without light) of the embodiment

[0057] Example <![CDATA[Evaporation rate (kg·m -2 ·h -1 )]]> Evaporation efficiency (%) Example 1 0.58 29.4 Example 2 0.53 23.9 Example 3 0.51 21.8 Example 4 0.31 17.6

[0058] Obviously, for those skilled in the art, the present invention can be improved or replaced without departing from the spirit or basic characteristics of the present invention, and these improvements or replacements should also be regarded as the protection scope of the present invention.

Claims

1. A method for preparing a laser engraved wood-based photothermal evaporator, comprising the following steps: Step 1), cutting the wood into 3 mm thick wood chips along the cross-section direction, and washing with deionized water to remove impurities, and then brushing the iron tannic acid ink on the upper surface of the wood; The wood chips are placed on a CO2 laser engraving machine, and the laser engraving machine is used to convert the surface of the wood chips into a graphitized carbon layer that can absorb sunlight; Step 2), heating and melting stearic acid in a water bath, and then dispersing the carbon nanotubes in the stearic acid at room temperature; Pour the graphene oxide dispersion into the above solution under magnetic stirring, continue stirring and transfer to a wide-mouth container, and dry excess water to obtain a SA-GO-CNTs solution; Step 3), the SA-GO-CNTs solution is evenly coated on the top layer of the laser-engraved wood, and after drying in an oven, a wood photothermal evaporator decorated with the SA-GO-CNTs photothermal coating is obtained.

2. The method for preparing a laser engraved wood-based photothermal evaporator according to claim 1, characterized in that: The wood in step 1) is poplar, and the wood substrate has a length of 2 cm, a width of 2 cm, and a height of 0.3 cm.

3. The method for preparing a laser engraved wood-based photothermal evaporator according to claim 1, characterized in that: Step 2) The mass ratio of stearic acid to carbon nanotubes is 11:1, the concentration of graphene oxide dispersion is 2 mg / ml, and the mass ratio of graphene oxide to carbon nanotubes is 1:

25.

4. The method for preparing a laser engraved wood-based photothermal evaporator according to claim 1, characterized in that: Step 2) The temperature of the magnetic stirring is 80° C. and the stirring time is 3 h.

5. The method for preparing a laser engraved wood-based photothermal evaporator according to claim 1, characterized in that: Step 2) The drying temperature is 60°C and the drying time is 18 hours.

Citation Information

Patent Citations

  • Titanium alloy sheet forming process based on continuous laser scanning

    CN103056521A

  • Multilayer body and its preparation method and use

    CN106256768A

  • Agriculture and forestry residue-based photo-thermal converted material for water treatment, preparation method and application thereof

    CN107443823A

  • Phase change thermal storage material applied to solar wood drying and preparation method

    CN108219751A

  • Method for fabricating metal layer on ceramic surface

    CN108601234A

Cited By

  • Laser carbonization evaporator with three-dimensionally fluctuant surface as well as preparation method and application of laser carbonization evaporator

    CN121948601A